Ethical Leadership and Employee Work-Related Attitudes: Examining The Role of Psychological Empowerment - Daniel GAJDA; Adrian PYSZKA (Communications of International Proceedings, 2023)
Ethical leadership could be crucial for achieving positive outcomes in organization because of its effects on employee’s work-related attitudes. Though considerable research has been conducted on ethical leadership, we still know very little about the processes through which a leader can foster these attitudes. Our study examines the effect of ethical leadership on employee attitudes such as motivation to work and organizational identification as well as verify the role of psychological empowerment as a potential mediator of examined relationships. We surveyed 730 employees from 33 large companies operating in Poland. The structural equation modeling was used to test the hypotheses. The results reveal that employee perception of ethical leadership positively affects motivation to work and organizational identification, while psychological empowerment partially mediates the impact of ethical leadership on both examined attitudes. Findings from our study proves that supervisors engaged in ethical leadership place their subordinates in positions where they can experience a sense of meaning at work, the feeling of competence in their jobs, and make them understand their impacts on their organization, and this enhanced feeling of empowerment in the employees can energize them to do their best in their work and foster the sense of belonging within the organization. Therefore, there is a need to develop ethical leadership reinforced by appropriate cultural patterns, values and norms, and open communication with employees, strengthening the intrinsic motivation of employees and their positive emotions.
Keywords: Ethical Leadership; Psychological Empowerment; Work Motivation; Organizational Identification